2015
DOI: 10.1179/1743294414y.0000000382
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of Cr–V–C–N films

Abstract: Quaternary Cr-V-C-N films were deposited on Si wafers through a hybrid system of arc ion plating and sputtering techniques in an Ar/N 2 /CH 4 gaseous mixture. In this work, the effects of vanadium on the microstructural evolution, mechanical properties and friction mechanism of Cr-V-C-N films were investigated. The results showed that quaternary Cr-V-C-N films consisted of nanosized crystallites of (Cr,V)(C,N) and amorphous VCN phases. The Cr-10?4 at-%V-C-N film possessed the higher hardness value of 34 GPa, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…However, the measured hardness of 28.3 (± 0.6) GPa is lower than the value given in a previous work reported by S.Y. Heo et al [16]. The difference between the two hardness values can be explained by the low compressive internal stress in grown coatings [32].…”
Section: Hardness and Young's Moduluscontrasting
confidence: 66%
See 3 more Smart Citations
“…However, the measured hardness of 28.3 (± 0.6) GPa is lower than the value given in a previous work reported by S.Y. Heo et al [16]. The difference between the two hardness values can be explained by the low compressive internal stress in grown coatings [32].…”
Section: Hardness and Young's Moduluscontrasting
confidence: 66%
“…Cr-N coatings with carbon and vanadium atoms embedded in a nanocrystalline Cr-V-N and Cr-C-N matrix. The structure of these coatings provides an extremely high hardness to these ternary systems and can prevent dislocation movements and micro-cracking, thereby improving their mechanical and tribological properties [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the nitrogen gas flow rate is around 16 sccm and r.f. negative bias voltages from 0 to -100 V are used, V access to the deposition surface is facilitated; hence, the fcc structure is determined by a partially ordered structure with V atoms, creating vacancies in nonmetallic sublattices [9,10]. On the other a b hand, it was observed that the V-C-N (111) peak position suffers a great deviation from bulk value for (VC and VN) materials, indicating thus a possible stress evolution of V-C-N single layers with the applied r.f.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%